Anamnestic, clinical and pathomorphological characteristics of malignant mammary tumors and dysplasia in dogs - Mykhalenko, N. I.; Kmitevych, E. O. (НУБіП України, 2019)
Parameters of 37 canine mammary malignant tumors and 13 dysplasia were compared. The age of an animal at the time of treatment in veterinary clinic, the age of the first factors of neoplasm, the number of births during life and the period of the last one, feeding nature, pseudo pregnancy and lactaton cases, the number and locaton of affected mammary gland, neoplasm macro characteristcs were considered. The size of the leter was determined with a view to three factors, the occurrence of capsules in neoplasms was ranked in points. The intensity of lactaton malfuncton was determined under the same method. Canine mammary dysplasia was examined at an earlier age than malignant tumors. This is partly due to the earlier onset than in the case of malignant tumors. At the same tme, period between cancer discovery and treatment in the later case was much shorter. It may state faster growth of tumors in case of malignancy than in mammary dysplasia. A significant difference in neoplasms size - malignant tumor and dysplasia is the proof thereof.Study of the influence of the number of births in the occurrence of different mammary neoplasms showed that dogs with dysplasia gave birth twice as less than those with diagnosed malignant tumors. The period between the last birth and identficaton of factors of disease for both groups of animals was the same. There was no significant difference also in the frequency of cases with lactaton malfuncton in dogs with mammary malignant tumors and dysplasia. Groups of animals with mammary malignant tumors and dysplasia differed on such characteristcs as frequency of tumors with full, partal or no capsule, and the average number of mammary gland affected and their localizaton.
Keywords: veterinary oncology; mammary tumors; malignant tumors; mammary dysplasia; dogs; собаки